A two‐yr prospective study of bone health in children after renal transplantation employing two imaging techniques. (22nd August 2013) - Christoforidis, Athanasios; Printza, Nikoleta; Gkogka, Chrysa; Kazantzidou, Eirini; Papachristou, Fotios
Abstract The aim of this study was to prospectively and longitudinally evaluate bone properties with the use of two bone imaging techniques (dual energy X‐ray absorptiometry [DXA], and quantitative ultraSonography [QUS]) in pediatric renal transplant recipients. Fourteen patients (eight boys and six girls) with a mean age of 12.25 ± 3.11 yr (range: 8–17.5 yr) completed a two‐yr follow‐up. Measurements of bone mineral density (BMD) by DXA at lumbar spine and hip and speed of sound (SOS) by QUS at radius and tibia were performed at the beginning and at the end of the study. A significant improvement in mean Z‐score of SOS values measured at tibia (1.01 ± 1.31 vs. −0.46 ± 1.14, p = 0.005) was observed. On the contrary, mean Z‐score of BMD values measured at femoral neck was significantly reduced (−1.95 ± 2.15 vs. −0.33 ± 1.13, p = 0.041). Finally, multivariate stepwise regression analyses showed that glomerular filtration rate at the beginning of the study was the best predictor of the difference in BMD Z‐scores measured at lumbar spine. Additionally, values of intact parathormone (iPTH) at the beginning of the study and the change in iPTH throughout the study predicted the 72.3% of the difference in Z‐score of SOS measured at radius with an inverse relationship.